KARAKTERISKTIK MUSIKAL PADA ALBUM KOMPILASI KARYA KOMUNITAS JAZZ JOGJA - Vivian, Yovi Irvan (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2015)
The musician and jazz musical lovers in Yogyakarta are stated in a music group named Jogja Jazz Community. Jogja Jazz Community community often presents the shows that are showed every week (Jazz Mben Senen and Etawa Jazz) and every year (NgayogJazz). This community existence isn’t only performed in live concert, but also by producing compilation album every year. Compilation album consists of some projects which participate in it. This research focuses on compilation album entitled Jazz Basuki Mawa Bea (2009) and Jazz